1969
DOI: 10.1128/aem.17.6.787-789.1969
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Nuclease Activity of Fish Spoilage Bacteria, Fish Pathogens, and Related Species

Abstract: The production of extracellular deoxyribonuclease and ribonuclease by 23 marine and 3 dairy strains of Pseudomonas putrefaciens, 15 strains of fish-pathogenic fluorescent pseudomonads, 38 strains of fluorescent pseudomonads isolated from haddock, and 34 related organisms was determined by an agar plate method. All strains of P. putrefaciens produced both deoxyribonuclease and ribonuclease. Of the other 87 organisms examined, 26.5 % produced ribonuclease and 14.5 % produced deoxyribonuclease. All organisms whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1972
1972
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The involvement of enzyme production in fish spoilage seems likely and research on the subject is necessary to further understand spoilage mechanisms with respect to geographic, as well as anatomical, origin. Previous studies have identified DNase‐ and protease‐producing bacteria on fish tissue stored at refrigerated temperatures . The ability of bacteria to produce extracellular enzymes during low temperature incubation increases damage to fish tissue due to bacterial growth as well as affect diversity among microbial populations.…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of enzyme production in fish spoilage seems likely and research on the subject is necessary to further understand spoilage mechanisms with respect to geographic, as well as anatomical, origin. Previous studies have identified DNase‐ and protease‐producing bacteria on fish tissue stored at refrigerated temperatures . The ability of bacteria to produce extracellular enzymes during low temperature incubation increases damage to fish tissue due to bacterial growth as well as affect diversity among microbial populations.…”
Section: Introductionmentioning
confidence: 99%